Afatinib-associated Stevens-Johnson syndrome in an EGFR-mutated lung cancer patient. (May 2016) - Doesch, Janine; Debus, Dirk; Meyer, Christian; Papadopoulos, Thomas; Schultz, Erwin S; Ficker, Joachim H.; Brueckl, Wolfgang M.
Highlights: Afatinib is a tyrosine kinase inhibitor for first-line therapy in advanced non-small cell lung cancer. Stevens-Johnson syndrome related to EGFR directed tyrosin kinase inhibitors as a rare adverse event. First case report of SJS during afatinib treatment. Abstract: Introduction: Afatinib is a tyrosine kinase inhibitor (TKI), that has been approved for treating patients with epidermal growth factor receptor (EGFR) mutated advanced non-small-cell lung cancer (NSCLC). Stevens-Johnson syndrome (SJS) related to EGFR directed TKIs is a rare adverse event. Case presentation: We report a case of a 79-year-old white female with EGFR-mutated, metastatic non-small-cell lung cancer treated with afatinib as first-line palliative treatment, who developed a SJS after two months of treatment. Discontinuation of the TKI and systemic glucocorticoid treatment led to improvement of symptoms and recovery. Conclusion: Severe adverse cutaneous drug reactions that predominantly involve the skin and mucous membranes during treatment with afatinib should alert clinicians to suspect SJS and react appropriately.